EFEKTIVITAS WAKTU TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (zea mays saccharata sturt) DAN KACANG TANAH (Arachis hypogaea) DALAM SISTEM TUMPANGSARI - Awidiyantini, Ruly; Kristiana, Lia; Nurmalasari, Yanti (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2023)
The effectiveness of planting time on the growth of production of sweet corn (zea mays saccharata sturt) and peanut (Arachis hypogaea) in an intercropping system, Ruly awidiyantini and Lia Kristiana, Agrotechnology Study Program, Faculty of Agriculture, Islamic University of Madura. peanuts is by several planting treatments and spacing. This study aims to determine the response of several planting treatments and plant spacing to the growth and production of maize (Zea mays) in an intercropping system with peanuts. The research method used a completely randomized design (CRD) consisting of 3 treatment levels, namely P0 planting at the same time, P1 planting a difference of 1 week and P2 a difference of 2 weeks. Parameters observed were plant height (cm), number of leaves (strands), weight of wet ear (g), and weight of dry ear (g). The results showed that the effectiveness of several treatments and planting time of sweet corn (Zea mays) in the peanut intercropping system gave a very significant effect on the parameters of sweet corn height, number of leaves, weight of wet cobs and weight ofdry cobs but had no significant effect on number of branches peanuts. The planting time treatment was still the most effective in responding to sweet corn (Zea mays) in the peanut intercropping system.